A karyotypic study on Silene sect. Sclerocalycinae in Turkey - (:unkn) unknown (WILEY, 2009)
The karyology of fifteen taxa of Silene sect. Sclerocalycinae from Turkey has been investigated. Karyotype analyses has been carried out and the chromosome number of Silene caramanica, S. peduncularis, S. armena, S. laxa, S. swertiifolia, S. caesarea, S. sclerophylla, S. haradjianii and S. lycaonica have been determined for the first time. For all the taxa studied, the diploid chromosome number and the basic chromosome number were found to be 2n=24 and x=12, respectively. Except for S. chlorifolia and S. doganii, the karyomorphology of the taxa studied is here described for the first time. S. laxa was found to have the smallest chromosomes whereas the largest ones were observed in S. haradjianii. Silene chlorifolia had the highest A(1) index and S. bupleuroides subsp. bupleuroides had the highest interchromosomal asymmetry coefficient (A(2)).
Keywords: SOUTH ANATOLIA; EAST ANATOLIA; CARYOPHYLLACEAE; TAXA